SUVOKIMO IR VAIZDUOTĖS SĄVEIKA: FENOMENOLCGINĖ PERSPEKTYVA IR PASĄMONĖS TYRINĖJIMAI. - Jonkus, Dalius (Problems / Problemos, 2014)
Two problems are investigated in the article. The first problem is the connection between perception and imagination. The second problem is the connection between imagination and the unconscious. Both problems are connected by the question whether the conscious can be reduced to the unconscious? Also the article criticises attempts to identify the consciousness with imagination. By reducing perception to imagination and the conscious to the unconscious we block the path for the phenomenological description of imagination and the unconscious, because we can only describe imagination from the perspective of perception, and unconsciousness can only be described from the perspective of consciousness as awareness. The representations of memories and imagination are also related with actual or possible angles of perception. The changing and variation of perspectives allows to uncover an invariant essence of things. But only by doing double reduction and relating visions of imagination or memories with perception and their associated meaning can we become aware of the desires submerged in the representations, which we do not admit as being our own.